2010
DOI: 10.1007/s11694-010-9100-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid extraction and detection of trace Chlorpyrifos-methyl in orange juice by surface-enhanced Raman spectroscopy

Abstract: It is estimated that 20-50% of crops are saved from infestation through the use of pesticides. However, US inspectors find that more than 4% of fruits and vegetables imported exceed concentration levels considered safe for human consumption. This represents millions of tons of food brought to market annually that cannot be inspected using current hour-long laboratory methods. In an effort to provide inspectors with a simple, fast, fieldusable analyzer and method, we have been developing a sampling device that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 22 publications
5
23
0
Order By: Relevance
“…However, quantification could be a challenge for in situ detection on surfaces (Liu and others ). For the detection of pesticides in liquid food matrices, Shende and others () used solvent extraction and solid‐phase extraction prior to SERS to extract and detect 50 ppb chlorpyrifos‐methyl intentionally added to orange juice in 12 min.…”
Section: Applications Of Sers In the Chemical Analysis Of Foodmentioning
confidence: 99%
“…However, quantification could be a challenge for in situ detection on surfaces (Liu and others ). For the detection of pesticides in liquid food matrices, Shende and others () used solvent extraction and solid‐phase extraction prior to SERS to extract and detect 50 ppb chlorpyrifos‐methyl intentionally added to orange juice in 12 min.…”
Section: Applications Of Sers In the Chemical Analysis Of Foodmentioning
confidence: 99%
“…For the applications in food matrices, many of the SERS studies still used a complex extraction procedure, which increased the analytical time (Liu and others , 2012b; Xie and others ), or achieved unsatisfactory sensitivity (Shende and others , ). A recent study reported a rapid SERS detection of 50 ppb chlorpyrifos‐methyl artificially added to orange juice in 12 min, including the time for solvent extraction and solid‐phase extraction (Shende and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Surface‐enhanced Raman scattering (SERS) is a spectroscopic technique where nanoscale metal particles are used to greatly enhance the Raman scattering of certain chemicals . The rich molecular information provided by Raman scattering and the increased sensitivity provided by surface enhancement from silver or gold nanoparticles has been successfully demonstrated for measurements of adulterated and contaminated food, drugs in saliva,explosive materials, and chemical and biological agents . Many of these measurements are being transitioned from the lab to the field and will likely employ portable Raman analyzers, virtually all of which use 785 nm laser excitation.…”
Section: Introductionmentioning
confidence: 99%